Imposing restrictions on density functions utilised in computing with words - Gemeinder, Marcus (Zielona Góra: Uniwersytet Zielonogórski)
Applying the generalised extension principle within the area of Computing with Words typically leads to complex maximization problems. If distributed quantities - such as, e.g., size distributions within human populations - are considered, density functions representing these distributions become involved.
Keywords: computing with words; approximate reasoning; generalised extension principle; resemblance